P63 modulates the expression of the WDFY2 gene which is implicated in cancer regulation and limb development. Issue 12 (13th December 2019) - Monti, Paola; Ciribilli, Yari; Foggetti, Giorgia; Menichini, Paola; Bisio, Alessandra; Cappato, Serena; Inga, Alberto; Divizia, Maria Teresa; Lerone, Margherita; Bocciardi, Renata; Fronza, Gilberto
Abstract: TP63 is a member of the TP53 gene family, sharing a common gene structure that produces two groups of mRNAs' encoding proteins with different N-terminal regions (ΔN and TA isoforms); both transcripts are also subjected to alternative splicing mechanisms at C-terminus, generating a variety of isoforms. p63 is a master regulator of epidermal development and homoeostasis as well as an important player in tumorigenesis and cancer progression with both oncogenic and tumour suppressive roles. A number of studies have aimed at the identification of p63 target genes, allowing the dissection of the molecular pathways orchestrated by the different isoforms. In the present study we investigated in more detail the p63 responsiveness of the WDFY2 ( WD repeat and FY VE domain containing 2 ) gene, encoding for an endosomal protein identified as a binding partner of the PI-3K/AKT signalling pathway. We showed that overexpression of different p63 isoforms was able to induce WDFY2 expression in TP53 -null cells. The p63-dependent transcriptional activation was associated with specific response elements (REs) that have been identified by a bioinformatics tool and validated by yeast- and mammal-based assays. Interestingly, to confirm that WDFY2 belongs to the p63 network of cancer regulation, we analysed the impact of WDFY2 alterations, by showing its frequent deletion in different types of tumours and suggesting its expression level as a prognostic biomarker. Lastly, we identified a chromosomal translocation involving the WDFY2 locus in a patient affected by a rare congenital limb anomaly, indicating WDFY2 as a possible susceptibility gene placed downstream p63 in the network of limb development.